A Study of In2O3 Nano Particles for Gas Sensor Application - Halbos, Raghad J.; Al-Algawi, Sariya; Rasheed, Rashed T.; Hassan, Ruqia Abdulhussien; Mahdi, Raghad R.; Azeez, Hasanain; Fayad, M. A. (Journal of Fuzzy Systems and Control, 2024)
In this research, the sol-gel technique was used to prepare indium oxide nanoparticles. In addition, these particles are deposited by (dip coating technique) on a quartz substrate. Several measurement instruments (FTIR, SEM, UV-visible, and X-RAY diffraction) were used in this study to diagnose and analyze the properties of indium oxide (In2O3) particles at different parameters. The results from XRD indicated that the particle formation converted to a polycrystalline phase at different annealing temperatures (200 ℃ and 600 ℃) for an hour and a half. Also, the XRD results show an increase in the (grain size and lattice constant) with increased annealing temperature. The measurements of the Hall Effect showed the type of conductivity of (In2O3) particles is N-type, carrier concentration, mobility, and resistivity. The results of the sensitivity of indium oxide thin films to toxic gas, specifically carbon monoxide (CO) gas, showed an increase in the sensitivity of thin films annealed at high temperatures.